International Monetary Fund Annual Report 1961. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1961)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1961. The report highlights that in contrast to the year 1959, when virtually all countries participated in worldwide expansion, the year 1960 and the early part of 1961 presented a less unified picture. Rapid growth continued in most of the European industrial countries and in Japan, but in the United States and Canada, a slackening of activity was evident. The volume of exports of the primary producing countries also increased.